Wildfowl counts in the British Isles - Atkinson-Willes, George (Wildfowl, 1954)
Wildfowl Counts were started in 1947 by the British Section of the International Wildfowl Inquiry Committee in an attempt to ascertain whether the populations of wildfowl wintering in this country were increasing, decreasing, or remaining unchanged. The original conception of regular monthly counts of wildfowl for a prolonged period as the best means of providing the necessary evidence remains sound and unaltered in the light of experience and is a striking credit to the foresight of its authors. Certain refinements in the uses to which the results may be put have been evolved since, but the original plan of comparing year by year the numbers of each species on selected waters remains the basis of the investigation.